Komunikasi Terapeutik Dalam Meningkatkan Pelayanan Keperawatan di RS. Mitra Medika Tanjung Mulia - Asrul, Asrul; Afriani , Miskah (Journal of Pharmaceutical and Sciences, 2024)
Through communication, relationships, and trust can be established between individuals. Communication plays a significant role, as every human has the inherent ability to communicate, even if methods vary widely. This is equally true for the demands of the nursing profession. Nurses are not only required to possess medical and health knowledge but must also demonstrate communication skills that are clear, effective, and purposeful. Additionally, nurses must maintain a high moral responsibility in their communication, characterized by empathy, compassion, and a willingness to assist.  This study aims to enhance the quality of nurse services in hospitals, particularly in addressing the diverse characteristics and physical or psychological conditions of patients, demanding effective communication skills to accurately understand and meet patient needs. Communication challenges among nurses present a serious issue, as poor communication can negatively impact patients’ comfort and, ultimately, their healing process.  This study utilizes an experimental method with a one-group pretest-posttest design. This design allows for the comparison of results before and after an intervention, helping to measure the impact of the treatment. The population includes all 266 inpatient nurses at Mitra Medika Tanjung Mulia Hospital in Medan, with a purposive sample of 59 nurses. Data analysis was conducted using paired t-tests. Results indicate that therapeutic communication plays a critical role in supporting patient recovery. To achieve this, nurses must continuously improve their knowledge and therapeutic communication skills within their clinical practice.